Hambatan yang Dihadapi ASEAN Defense Industry Collaboration (ADIC) dalam Menentukan Platform Persenjataannya - Novri Surya Ningsih (Jurnal Hubungan Internasional, 2019)
This article is a study of the impediments to the ASEAN Defense IndustryCollaboration (ADIC) in determining its weapons platforms. In analyzingthe impediments, this article refers to the concept of Revolution in MilitaryAffairs (RMA) which formulates that the technology, doctrine, andmilitary organization are influenced by each member of the ADIC. TheRMA is a useful concept for portraying the military characteristics ofeach member. The causality constructed in this research is between thedoctrinaire, technological, and organizational features in the determinationof military and weapons platform in the ADIC. This article findsthat there is discrepancy in existing technologies, doctrines, and militaryorganizations among members of ADIC and it creates a strong impedimentin determining weapons platforms. Without initiating strongercollaboration and setting tangible policy aims to solve common groundabsence, ADIC will not go effectively.